How effective the problem-based learning (PBL) in dental education. A critical review - Ali Alrahlah (Elsevier, 2016)
The purpose of this critical review is to explore the research supporting the effectiveness of problem-based learning (PBL) as a teaching method in dental education. PBL was developed more than 40 years ago in reaction to the problems and limitations of traditional teaching approaches. Here, aspects of the PBL teaching approach are reviewed, and the reasons for the substantial effect of this approach on dental education are discussed. Evidence shows that students in PBL-based courses exhibit superior professional skills and effective learning compared with those instructed using traditional approaches. Keywords: Dental education, Problem-based learning, Effectiveness, Critical review